Advantages of Ultrafast™ ultrasound in the screening for renal artery disease - Ivanac Gordana; Bulum Antonio; Jagnjić Ana Bojko; Vujević Filip; Lucĳanić Marko; Bulum Marta; Ivanac Krešimir; Brkljačić Boris; Divjak Eugen (Journal of Ultrasonography)
Renal artery disease is the most common cause of secondary hypertension worldwide. B-mode and Doppler ultrasound are considered the modalities of choice for the imaging of the renal arteries. However, an adequate examination can be plagued by difficulties in patients with unfavorable anatomy. UltraFast™ ultrasound is faster, performed with higher frame rates, and enables prospective and retrospective data analysis with quantification of flow data in the obtained image, so it may be able to resolve some of the difficulties encountered during conventional ultrasound examinations in patients with suspected renal artery disease.